Evaluating the long-run impact of an innovative anti-poverty programme: Evidence using household panel data - Asadullah, M Niaz; Ara, Jinnat (Taylor & Francis Online, 2022)
This article was published in The Applied Economics and the definite version is available at: https://doi.org/10.1080/00036846.2015.1073846 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/00036846.2015.1073846?scroll=top&needAccess=true